Study of workplace violence, its risk factors and perceptions about workplace security in doctors of Paithan - Pund, Sandeep B.; Kuril, Bina M.; Doibale, Mohan K.; Ankushe, Rajendra T.; Kumar, Purushottam; Siddiqui, Nafeha (International Journal Of Community Medicine And Public Health, 2017)
Background: Of all work settings, hospitals carry the greatest risk of verbal abuse and threats, with 73% of staff on medical premises suffering abuse. The scenario in Indian subcontinent is also not so bright. Doctors are frequently assaulted in India as well where doctors are shot, even stabbed. Thus this study was undertaken to know the exact prevalence of such incidences in Paithan taluka of Aurangabad district. Methods: A community based cross-sectional study was done in the Paithan taluka of Aurangabad district in Maharashtra from October 2015 to December 2015. All the doctors in the urban as well as rural areas of Paithan were interviewed to know their experiences about episodes of workplace violence (WPV) during last 12 months as well as their lifetime experiences. Some of the factors associated with the WPV were also asked along with the perceived reasons for such type of incidences. Results: The prevalence of workplace violence in the last 12 months was found to be 63.41%, whereas the lifetime prevalence was found to be 78.05%. It was observed that 21.95% of the doctors were demanded for extortion money and 11.27% experienced intentional destruction of their hospital property. Workplace violence was seen to be significantly more associated with younger doctors, highly educated doctors, doctors in government service and doctors with comparatively lesser practice experience. Lack of communication was perceived by the doctors as the most common reason for these incidences. Conclusions: Workplace violence is emerging as a bane to the medical profession and has to be dealt with urgently. Poor communication with patients along with other factors should be dealt with to mitigate this problem.